A New Garber-Style Solution to the Problem of Old Evidence. Issue 4 (October 2015) - Hartmann, Stephan; Fitelson, Branden
Abstract : In this discussion note, we explain how to relax some of the standard assumptions made in Garber-style solutions to the Problem of Old Evidence. The result is a more general and explanatory Bayesian approach.